Extended-Release Injectable Naltrexone (XR-NTX) With Intensive Psychosocial Therapy for Amphetamine-Dependent Persons Seeking Treatment: A Placebo-Controlled Trial. Issue 3 (May 2017) - Runarsdottir, Valgerdur; Hansdottir, Ingunn; Tyrfingsson, Thorarinn; Einarsson, Magnus; Dugosh, Karen; Royer-Malvestuto, Charlotte; Pettinati, Helen; Khalsa, Jag; Woody, George E.
Abstract : Objective: Explore the efficacy of extended-release injectable naltrexone (XR-NTX) for preventing relapse to amphetamine use. Method: Clinical trial of 100 amphetamine-dependent, treatment-seeking patients who were randomized to 6 monthly 380 mg doses of XR-NTX or matching placebo before entering intensive outpatient after varying lengths of inpatient treatment in Reykjavik, Iceland. Weekly urine drug tests, retention, and standardized instruments assessed efficacy. Results: Of 169 approached, 100 were randomized. Although amphetamine dependence was the main reason for seeking treatment, three-quarters or more of participants had 1 or more other substance dependencies. Of 51 randomized to XR-NTX, 20 received 4 or more injections; of 49 assigned to placebo, 26 received 4 or more injections. Of the planned 2400 weekly urine drug tests, 1247 were collected (52%); 4% of these were positive for amphetamine, 8% for benzodiazepine, 7% for marijuana, 1% for cocaine, and 1% for opioid. XR-NTX had no effect on amphetamine-positive tests, retention, or other outcomes. Those providing half or more of their tests attended more weeks of treatment than those providing less than half of their tests ( m  = 10.76 vs 3.31; t (92) = 5.91, P  < 0.0001), and 92 participants provided at least 1 test. Conclusions: Adding XR-NTX to the usual combination of inpatient and intensive outpatient treatment did not reduce amphetamine use. The low prevalence of substance use among collected urine samples, and the association between collected samples and weeks in treatment, was consistent with other studies showing that staying in treatment is associated with better outcomes.